2015
DOI: 10.1175/jas-d-14-0284.1
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Tropical Cyclone Activity to Off-Equatorial Thermal Forcing in Aquaplanet Simulations

Abstract: The sensitivity of global tropical cyclone (TC) activity to changes in a zonally symmetric sea surface temperature (SST) distribution and the associated large-scale atmospheric circulation are investigated. High-resolution (~50-km horizontal grid spacing) atmospheric general circulation model simulations with maximum SST away from the equator are presented. Simulations with both fixed-SST and slab ocean lower boundary conditions are compared. The simulated TCs that form on the poleward flank of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 40 publications
6
47
1
Order By: Relevance
“…A northward shift in GPI is noticeable in the eastern North Pacific, unsurprisingly associated with the local shift in ITCZ. This shift in the ITCZ would be expected to not only impact the genesis of storms (Merlis et al, 2013) but also their intensity (Ballinger et al, 2015). A slight decrease in genesis potential is seen in the North Atlantic.…”
Section: Mid-holocenementioning
confidence: 99%
“…A northward shift in GPI is noticeable in the eastern North Pacific, unsurprisingly associated with the local shift in ITCZ. This shift in the ITCZ would be expected to not only impact the genesis of storms (Merlis et al, 2013) but also their intensity (Ballinger et al, 2015). A slight decrease in genesis potential is seen in the North Atlantic.…”
Section: Mid-holocenementioning
confidence: 99%
“…SST gradient in the tropics and a lower SST at the poles compared to idealized aquaplanet simulations of Li et al (2013) and Ballinger et al (2015). The former difference yields a larger number of tropical cyclones, while the latter mimics the effect of absent sea ice.…”
Section: Experimental Designmentioning
confidence: 86%
“…The increase, which averages~3.7 TCs per season (August-October), is mainly associated with an increase of TC formation in the subtropics between 30°N and 40°N. Earlier studies suggested that such an increase of subtropical activity could occur with a reduced meridional gradient of the extratropical SST (Ballinger et al, 2015;Fedorov et al, 2018) or a globally warmed climate (e.g., Yoshida et al, 2017). The development of these TCs may be related to subtropical cyclones (Guishard et al, 2009;Bentley et al, 2016), which contributed nearly 50% of TCs in the recent 2018 hurricane season.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…TC formation in the subtropics potentially can cause unexpected damage in regions where TC activity is usually rare (e.g., Hurricane Leslie). Earlier studies suggested that such an increase of subtropical activity could occur with a reduced meridional gradient of the extratropical SST (Ballinger et al, 2015;Fedorov et al, 2018) or a globally warmed climate (e.g., Yoshida et al, 2017).…”
Section: Summary and Discussionmentioning
confidence: 99%